ANALISIS DEFECT PRODUCT DENGAN QUALITY CONTROL CIRCLE TERHADAP PROSES PRODUKSI MASKER DI PT. XYZ - Pagar Bagus Akbar, (2023)
In the world of manufacturing, it cannot be separated from production process activities, production process activities are activities that aim to produce goods to meet demand. The purpose of this study is to identify the causes of defective products at PT XYZ, analyze the factors that are the top priority as a basis for improvement using Fault Tree Analysis and provide input using the Quality Control Circle method to reduce defective products at PT XYZ. All business scales have a priority in improving the quality of the products produced. PT XYZ is a company engaged in manufacturing to produce personal protective equipment. Based on the calculation of the paretto diagram, it is known that the most dominant defect is the not good rope defect with a value of 51% and the non-dominant defect is chipped with a value of 23%. The types of defects that often occur in PT XYZ's production are NG ropes with a total of 41,939 pcs, followed by 21,667 pcs of stuck material, and 19,069 pcs of chipped.